Motivational component profiles in learning embryology: A comparative study between first and final year medical students - Dinesh Kumar V; Raveendranath V; Niranjan Biswal (Tabriz University of Medical Sciences, 2023)
Background: As a part of the "triangulation approach" for remodeling teaching-learning pedagogy related to embryology, we conceived the idea of comparing the motivational component profiles of first-year and final-year students, who might have realized the salience of learning embryology after seeing remarkable cases of congenital malformations. Methods: We used an observational study design for assessing the interrelation of motivational component profiles between both cohorts using the Science Motivation Questionnaire II (SMQ II)1. Of the total sample size of 150 first-year students, 126 agreed to participate, and similarly, out of 150 final-year students, 105 had consented to participation ['convenience' model of sampling]. The measures of central tendency, i.e., mean and standard deviation, were calculated for each item, and the Mann-Whitney test was utilized to compare the mean score of each motivational component. Results: Our results indicate that the overall motivational profile for learning embryology differs among first and final-year students. The mean intrinsic motivation and self-determination scores were slightly higher in the first-year cohort, whereas self-efficacy scores were slightly higher in the final-year cohort. This information integrates students' levels and types of motivation into the planning, delivery, and evaluation of medical education. Conclusion: Despite being one of the key components of self-regulated learning, motivational component profiles remain unaddressed in contemporary medical education owing to their abstractness and subjectivity in terms of documentation. The current study helped us envisage the difference in motivational component profiles toward learning embryology in cross-section. It also senses the need for incorporating motivational short courses in undergraduate curricula, especially in remediation programs.